Gender gaps in the individual pension system in Turkey - Adem Y. Elveren; Sara Hsu (The University of Utah, Department of Economics, 2007)
This paper examines the gender implications of Turkeys private pension scheme introduced in 2003 as a part of ongoing social security reform. While there is a growing literature on Turkeys social security reform, there are no studies on the gender dimension of social security and gender effects of reform. By examining the gender gap in benefits that arise from the defined contribution schemes in a series of projections, this study seeks to address this gap. This paper first reviews the literature on gender inequality in social security systems. In Section 2, we present a brief history of the social security in Turkey and the Individual Pension System. Section 3 outlines the model, which is a series of projections given gender differences in contributions over time. The final section is dedicated to summarizing the results and discussion.
Keywords: 330